Method for voltage control in charge circuit of electric discharge installations with two capacitors under nonzero initial conditions - Suprunovska, N.I.; Shcherba, M.A. (Електротехніка і електромеханіка, 2018)
Purpose. To analyze the transient processes in the charge circuit of electric discharge installations with two capacitors, taking into account the change in the initial conditions of such processes (initial voltage on the capacitors and the initial current in the charge circuit) as well as to develop the method for charge voltage control of such installations using purposeful change of these initial conditions. Methodology. We have applied the concepts of theoretical electrical engineering, the principles of theory of electrical circuits, and mathematical simulation in the software package MathCAD 12. Results. We have obtained analytical expressions and graphical dependencies establishing a quantitative relationship between the value of the maximum charge voltage of an electric discharge installation and the values of the initial voltage on its capacitors and the initial current in the circuit. This allows us to propose the method for the charge voltage control of electric discharge installations with two reservoir capacitors, using a purposeful change in their initial voltages and initial current in the charge circuit. Originality. For the first time, we have found that the charge voltage of the installation can be controlled using two influence mechanisms – either changing the initial current in the charge circuit (by interrupting the transient process of the first capacitor charge at a certain time) or using a nonzero initial voltage on the charged second capacitor. In this case the charge voltage can be varied by 2 times. Practical value. The use of this method makes it possible to obtain discharge pulses of complex shape in the technological load, since the maximum charge voltages of the first capacitor and second one can differ by a factor of 1.5.